In vivo open- and closed-chest measurements of left-ventricular myocardial viscoelasticity using lamb wave dispersion ultrasound vibrometry (LDUV): a feasibility study. (30th April 2018) - Nenadic, Ivan Z; Urban, Matthew W; Pislaru, Cristina; Escobar, Daniel; Vasconcelos, Luiz; Greenleaf, James F
Abstract: Diastolic dysfunction causes close to half of congestive heart failures and is associated with increased stiffness in left-ventricular myocardium. A clinical tool capable of measuring viscoelasticity of the myocardium could be beneficial in clinical settings. We used Lamb wave Dispersion Ultrasound Vibrometry (LDUV) for assessing the feasibility of making in vivo non-invasive measurements of myocardial elasticity and viscosity in pigs. In vivo open-chest measurements of myocardial elasticity and viscosity obtained using a Fourier space based analysis of Lamb wave dispersion are reported. The approach was used to perform ECG-gated transthoracic in vivo measurements of group velocity, elasticity and viscosity throughout a single heart cycle. Group velocity, elasticity and viscosity in the frequency range 50–500 Hz increased from diastole to systole, consistent with contraction and relaxation of the myocardium. Systolic group velocity, elasticity and viscosity were 5.0 m s −1, 19.1 kPa, 6.8 Pa · s, respectively. In diastole, the measured group velocity, elasticity and viscosity were 1.5 m s −1, 5.1 kPa and 3.2 Pa · s, respectively.